Internalization of Akhlak Values in Islamic Education: Al-Ghazali’s Perspective for Addressing Moral Crisis - Nazarudin, Luthfi; Mukarom, Mukarom (IQRO: Journal of Islamic Education, 2026)
The moral crisis among the younger generation has become a major challenge in contemporary Islamic education, as reflected in the increasing cases of violence, bullying, and drug abuse among adolescents. Although many studies have explored moral education from conceptual and empirical perspectives, limited research has systematically reconstructed classical Islamic ethical thought to address contemporary moral challenges shaped by digitalization and rapid social change. In particular, the moral philosophy of Al-Ghazali has rarely been formulated into an integrative framework for modern Islamic education. This study aims to reconstruct Al-Ghazali’s concept of moral internalization and examine its relevance in responding to the moral crisis among the younger generation. Using a qualitative library research method, this study analyzes classical texts of Al-Ghazali and relevant scholarly literature through a descriptive-analytical approach. The findings indicate that moral internalization through character education, moral habituation, exemplary conduct (uswah hasanah), and tazkiyatun nafs provides a conceptual framework for strengthening students’ moral development. This study contributes theoretically by offering a reconstructed model of Al-Ghazali’s moral framework that is adaptable to contemporary Islamic educational contexts.